A Performance Study of Micro-Small-Medium-Enterprises (MSMEs) in Emerging Economy: Role of Entrepreneurial Orientation - Sunyoto, Hadi Kusuma (Universitas Sam Ratulangi, 2024)
The role of MSMEs in economic growth across the world has become more critical over recent years because of the intensively changing business environment. MSMEs especially in Indonesia have contributed to reducing the unemployment rate. However, the problem of MSMEs is maintaining their businesses because of inefficiency in operating and producing competitive advantage. This research aims to examine the performance of MSMEs in emerging economies, particularly Surabaya City, Indonesia. The dimensions of entrepreneurial orientation were used to measure firms’ performance. They are proactiveness, innovativeness, risk-taking, autonomy, and competitive aggressiveness. The multiple linear regression analysis, classic assumption test, and purposive sampling technique were applied in this research. The findings of this study indicate that innovativeness, risk-taking, autonomy, and competitive aggressiveness variables significantly influence firms’ performance. Only the proactiveness variable was found not significant.